Economy-wide implications of biofuel production in Zambia - Hartley, Faaiqa; van Seventer, Dirk; Samboko, Paul Chimuka; Arndt, Channing (Routledge, 2019)
Potential biofuel demand in South Africa is estimated to increase to 1550 million litres by 2025 due to mandatory blending rates. Land and water constraints, however, limit the ability for domestic production. Zambia, due to its abundance in land, suitable climate, supportive set of bioenergy incentives and close geographical location to South Africa, has the potential to meet this increase in demand. Using a dynamic recursive computable general equilibrium model, we estimate the macro- and socio-economic impacts of bioethanol production in Zambia from three potential crops: sugarcane, cassava and sweet sorghum. The results show that the development of a single product bioethanol industry has the potential to increase economic growth without negatively affecting overall food security. Further expansion of the industry to multiple products results in larger gains to growth and welfare.